Assessment of Uncertainty in Illness and its Correlated Factors among Patients with Cancer at Tertiary Level Hospitals (Delta Medical College Journal, 2025)
Background: Patients with cancer have great experiences of uncertainty in illness rather than the disease, which can have negative impacts on their psychological adjustment, quality of life and disease outcome. Objective: The aim of the study was to determine the relationship between illness uncertainty and its related factors among these patients. Materials and method: A cross-sectional study was conducted among 120 cancer patients from Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Data was collected by in depth interview through questionnaire. Data analysis was done using t-test, ANOVA, and correlation test. Results: The average score of uncertainty among cancer patients was 99.3 with a range of 63 to 136. Younger participants had significantly higher uncertainty in illness than elder ones (r = -25, p= 0.01). Male patients had higher uncertainty when compared to female (t= -3.35) and it was statistically significant (p=0.02). Uncertainty in illness was significantly higher (t=0.29, p=0.02) among participants who had metastasis than who had no metastasis. Conclusion: This study reveals that patients with cancer experience significant levels of uncertainty in illness and their perceptions are affected by various factors.Delta Med Col J. Jul 2022;10(2): 45-51